Output Voltage Regulated Sepic Converter for Photovoltaic Systems - Duranay, Zeynep Bala (Institute of Electrical and Electronics Engineers Inc., 2021)
Voltage regulation at the output of a single ended primary inductor converter (SEPIC) is studied in this paper for the photovoltaic energy system. The designed converter output voltage is regulated to a constant value regardless of its input. Two loop control, one for voltage and one for current loop is used for the regulation system. This control technique is used to improve converter performance in case of system parameter variations. The design procedure is provided for SEPIC converter operating in continuous conduction mode. The system is implemented in Matlab/Simulink. The simulations have been done with various operating conditions. Results show that the PV system with SEPIC provides good regulation performance regardless of disturbances. © 2021 IEEE.
13th International Conference on Electronics, Computers and Artificial Intelligence, ECAI 2021 -- 1 July 2021 through 3 July 2021 -- Pitesti -- 171421
Keywords: dc-dc converter; multiloop control; photovoltaic; PI control; SEPIC converter